Regulation of mitochondrial morphology and metabolism by Jak-STAT pathway - Kun Do Rhee (The Korean Society of Animal Reproduction and Biotechnology, 2021)
Jak-STAT pathway is required for embryogenesis, female gametogenesis, cytokine-mediated neuroprotection, diabetes, obesity, cancer, stem cell, and various tissues. The noncanonical role of Jak-STAT in mitochondria function was supported by the detection of STAT protein in mitochondria, however, several studies show that STAT protein is detected in the endoplasmic reticulum (ER), and not in mitochondria. STAT protein may alter mitochondria function without entering mitochondria, this involves regulation of fission and fusion proteins to change mitochondria morphology. However, how changes in mitochondria morphology lead to changes in mitochondria metabolism needs further investigation.